2021
DOI: 10.1371/journal.pcbi.1009190
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty-based model of the effects of fixation on choice

Abstract: When people view a consumable item for a longer amount of time, they choose it more frequently; this also seems to be the direction of causality. The leading model of this effect is a drift-diffusion model with a fixation-based attentional bias. Here, we propose an explicitly Bayesian account for the same data. This account is based on the notion that the brain builds a posterior belief over the value of an item in the same way it would over a sensory variable. As the agent gathers evidence about the item from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Our results also provide insight into the dynamic implementation of attentional control. Previous work has shown that within-trial attentional dynamics play an important role in both decision making (Callaway et al, 2021; Krajbich et al, 2010; Li and Ma, 2021; Westbrook et al, 2020) and cognitive control (Adkins and Lee, 2021; Hardwick et al, 2019; Servant et al, 2014; Weichart et al, 2020; White et al, 2011). These foundational experiments have largely focused on spatial attention, with far less known about the dynamics of feature-based attention, where processing of targets and distractors is less mutually constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also provide insight into the dynamic implementation of attentional control. Previous work has shown that within-trial attentional dynamics play an important role in both decision making (Callaway et al, 2021; Krajbich et al, 2010; Li and Ma, 2021; Westbrook et al, 2020) and cognitive control (Adkins and Lee, 2021; Hardwick et al, 2019; Servant et al, 2014; Weichart et al, 2020; White et al, 2011). These foundational experiments have largely focused on spatial attention, with far less known about the dynamics of feature-based attention, where processing of targets and distractors is less mutually constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to the role of uncertainty on choice has been suggested in a recent study by Li and Ma (2021), who proposed a model in which the decision maker chooses based on a comparison of the subjective utility of each option. In their model, utility is a This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Relation To Other Models and Additional Ddm Variantsmentioning
confidence: 99%
“…Here we show that, as with attention, the influence of value confidence on choice critically depends on a decision-maker's expectations. This finding speaks against uncertainty aversion (or its converse, confidence bonus) as the main driver of choice variability associated with value confidence (Li & Ma, 2021). Rather it suggests a more nuanced role for value confidence in decision-making.…”
Section: Discussionmentioning
confidence: 81%
“…Like attention, value confidence has been proposed to confer a choice benefit at least as long as options are appetitive (Lee & Coricelli, 2020;Li & Ma, 2021). On its face, this proposal resonates with ubiquitous uncertainty aversion, as well as the idea that confidence itself may be a value signal (Lebreton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation